Design, Synthesis of Some New Quinazolinone Derivatives and Evaluation of their Antibacterial Activity - Mohammed, Aseel Jassim; Al-Jeilawi, Oday H.R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The novel quinazolinone derivatives were synthesized in excellent yields, manufactured, characterized, and investigated for their biological activity. This study aims to produce new quinazolinone derivatives and study their antibacterial activity. Quinazolinone derivatives were synthesized in three steps: the first step included the reaction of methyl anthranilate with isothiocyanatobenzene to produce a thiourea derivative (A1). In the second step (A1) was reacted with hydrazine hydrate to synthesized 3-Amino-2-(phenylamino) quinazolin-4(3H)-one (A2). The third step consisted of the reaction of (A2) with various organic compounds (phenylisotiocyanate, phenylisocyanate, acid halide, benzyl halide, and alkyl halide derivatives) to produce new derivatives. FT-IR, 1HNMR, and 13C NMR spectroscopy were used to identify the chemical structure of these compounds. The agar well diffusion technique was used to determine the antibacterial activity levels exhibited by the samples. Staphylococcus aureus and Escherichia coli were used as test organisms in this study. When compared to the antibiotic used as a standard, amikacin, these compounds demonstrated superior antibacterial activity.